2015
DOI: 10.1111/azo.12128
|View full text |Cite
|
Sign up to set email alerts
|

Limb and digit orientation during vertical clinging in Bibron's gecko, Chondrodactylus bibronii (A. Smith, 1846) and its bearing on the adhesive capabilities of geckos

Abstract: Russell, A.P. and Oetelaar, G.S. 2016. Limb and digit orientation during vertical clinging in Bibron's gecko, Chondrodactylus bibronii (A. Smith, 1846) and its bearing on the adhesive capabilities of geckos. -Acta Zoologica (Stockholm) 97: 345-360.Geckos with subdigital adhesive pads can scale smooth vertical surfaces in defiance of gravity. The deployment of the adhesive system is activated by the musculoskeletal system during active traverses of such surfaces, but adhesion on such substrata can also be achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 32 publications
0
38
2
Order By: Relevance
“…Furthermore, the modulation of foot orientation is also an important biological principle that promises to be very useful for technical application [33]. The characteristic structure of the pes and manus of the gecko, allowing the feet to rotate freely and the digits to be spread widely [47], leads to the animal's ability to adhere in the head up and head down orientation as well as on vertical surfaces [48]. Observation in tree frogs showed that they are unable to adhere to smooth surfaces in the head-down orientation [49], probably due to the constraint in digit spread and foot alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the modulation of foot orientation is also an important biological principle that promises to be very useful for technical application [33]. The characteristic structure of the pes and manus of the gecko, allowing the feet to rotate freely and the digits to be spread widely [47], leads to the animal's ability to adhere in the head up and head down orientation as well as on vertical surfaces [48]. Observation in tree frogs showed that they are unable to adhere to smooth surfaces in the head-down orientation [49], probably due to the constraint in digit spread and foot alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, digital spreading permits the ability to increase the size of individual toepads (Webster et al, 2009). The importance of the spread of the digits for padbearing lineages is apparent, because it permits the engagement of the adhesive apparatus in a variety of orientations simultaneously (Birn-Jeffery & Higham, 2014;Russell & Oetelaar, 2015;Zhuang & Higham, 2016). Larger species may benefit from greater support provided by toepads applied in opposing directions, which may also facilitate changing directions quickly (Imburgia et al, 2019;Russell & Oetelaar, 2015).…”
Section: Effect Of Sizementioning
confidence: 99%
“…A study similar to that of Powell et al (2018), examining ontogenetic growth in such species, with the simultaneous measurement of metatarsal head shape and interdigital angle measurement, could help determine the mechanisms underlying changes in interdigital angles. In addition, behavioral analyses, similar to that of Russell and Oetelaar (2015), would reveal how such species use their claws in combination with the broad digital spread that they possess (Naylor & Higham, 2019).…”
Section: Effect Of Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Geckos move in a variety of complex habitats, and often do so by employing an adhesive apparatus located on the ventral surface of the toes Higham, 2014, 2016;Russell, 2002;Russell and Higham, 2009;Russell and Oetelaar, 2015;Zhuang and Higham, 2016). The combination of visual and locomotor specializations makes geckos an ideal group for quantifying the relationship between the two.…”
Section: Introductionmentioning
confidence: 99%